(untitled) (Progressive Agriculture, 2021)
Zebrafish, Danio rerio belonging to the family Cyprinidae is one of the most important native ornamental model species used in fisheries research globally. The present study was conducted to evaluate the effects of sex ratio on the spawning of zebrafish and to observe the ovarian maturity in the laboratory condition. This experiment was conducted for 12 weeks in the glass aquaria (25×16×26 cm3 in size) and the zebrafish were reared in five different sex ratio treatments like -T1 (1m:1f), T2 (1m:2f), T3 (1m:3f), T4 (2m:1f) and T5 (3m:1f) and the fertilized eggs were collected daily from the aquaria. The results showed that mean number of eggs was found to be highest at T3 (821±67.11) and the average egg lay day interval was 1.9 days which significantly (p<0.05) differ from other treatments. These research findings will provide a guideline to small scale fish farmers, entrepreneurs and hatchery owners to develop the spawning of zebrafish in the laboratory settings with a little investment. It will also provide opportunities to construct zebrafish hatchery and produce commercially zebrafish fry in a large extent. Progressive Agriculture 32 (1): 78-83, 2021